UJI AKTIFITAS ANTI RAYAP TEMBAKAU DAN SALAK MADURA - Diana Nurus Sholehah (Agrovigor, 2011)
This study aims to determine the anti-termite potency of agricultural waste material that has not been used optimally, such as root and stem bark of tobacco and snackfruit rind to increase its economic value. The research conducted at the Laboratory of Agricultural Faculty Agroekoteknologi Trunojoyo. The study was designed based on completely randomized design (CRD) with 3 replication. The observation parameter is the number of termite mortality and weight reduction in test paper which is used as termite bait.  The results showed that the extract of root and stem bark Madura tobacco and snackfruit rind cause termite mortality was not significantly different ie consecutive 77.3% and 81.3% classified as strong termite. During the activity test, there is no weight reduction test paper so that termite mortality effect could be due to toxic effects of extract contacts.